UNJUK KERJA KOMBINASI METODE BASE64 ALGORITMA VIGNERE CHIPER DAN RAILFENCE CHIPER DALAM PENGAMANAN DATA VIDEO - Zulfahmi Syahputra; Supiyandi Supiyandi (Jusikom : Jurnal Sistem Komputer Musirawas, 2023)
Video files are information in the form of Video, Information becomes very vulnerable to be known, retrieved or even manipulated and misused by other parties who are not entitled. In this research combines the classic algorithm vigenere cipher with modren algorithm that is Railfance algorithm in securing video files, with the system built then every video file uploaded into the system will be translated into binary code with base64 technique which is plaintext and then will be encrypted with vigenere cipher algorithm and continued encryption using railfance algorithm and produce video file that can not be played , so Video files are considered damaged, when not. For decryption and vice versa video files that can not be played dupload into the system will be translated into binary code with base64 technique which is plaintext and then decrypted with railfance algorithm and continued decryption using vigenere cipher algorithm and produce video files that can be played. Key Word : video File, Base64, Algoritma Vigenere Cipher, Algoritma Railfance